The Mechanism of Mg2Al3 Formation by Mechanical Alloying - H. Suwarno; W.A. Adi; A. Insani (Atom Indonesia, 2009)
Synthetic and characterization of the Mg2Al3 formation by mechanical alloying have been carried out using a high energy ball milling process. Mechanical alloying is a technique of solid state reactions among two or more metals to form a new alloy through the deformation properties of the metals. The Mg2Al3 alloy was formed by milling the individual constituents using a high energy ball milling under the varied milling time of 10, 20 and 30 h. The refinement results on the x-ray diffraction analysis show that the observation and calculation are fit to each other. After milling for 10, 20 and 30 h the mixed Mg and Al metals are converted into Mg2Al3 at the composition of 71.82, 90.73 and 96.19 wt%. It is concluded that the Mg2Al3 alloy can be performed by high energy mechanical alloying after 30 h of milling. The mechanism of the Mg2Al3 formation is discussed. Received: 14 August 2008; Revised:12 November 2008; Accepted: 11 December 2008